PENGARUH RETURN ON EQUITY (ROE) DAN EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM PADA PT MAYORA INDAH Tbk PERIODE TAHUN 2013-2022 - Ariana, Ria; Noryani (Journal of Research and Publication Innovation, 2024)
This research aims to determine the effect of Return On Equity (ROE) and Earning Per Share (EPS) on share prices at PT Mayora Indah Tbk. either partially or simultaneously, the independent variables tested are: Return On Equity (ROE) and Earning Per Share (EPS), while the dependent variable used is Share Price. The sample in this research is PT Mayora Indah Tbk which is listed on the Indonesia Stock Exchange (BEI). The type of research used in this research is causal associative research using quantitative methods. The data used is secondary data in the form of the financial reports of the company PT Mayora Indah Tbk from 2013 to 2022. Data management is processed using the Statistical Product And Service Solution (SPSS) software program version 22.0. The data analysis used is the classical assumption test, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing (t test and f test). Based on the data obtained, the results of testing the classical assumption show that the data is normally distributed, there are no problems with multicollinearity, heteroscedasticity and is free from autocorrelation. Partially, Return On Equity (ROE) has an influence on share prices. This is proven by the t count value -2.615 > t table 2.364 and Earning Per Share (EPS) has a significant effect on share prices, this is proven by the t count value 12.506 > t table 2,364. Simultaneously, the Return On Equity (ROE) and Earning Per Share (EPS) variables have a significant effect on share prices. This is indicated by the f count value of 82.885 > f table of 4.74. The test value for the coefficient of determination or R2 was 95.9%, while the remaining 4.1% was influenced by other factors not explained in this study.